The role of China in the Portuguese speaking African countries: the case of Mozambique (Part I) - Ilhéu,Fernanda (2010)
Due to the Reform and Open Door Policies initiated in 1978, China recorded since then a fast sustainable economic growth, turning it into the worlds second largest economy. With an export oriented economic model, highly supported by Foreign Direct Investment, China became worlds number one exporter, after surpassing Germany in 2009. Presently China has the worlds largest foreign exchange currency funds, 50% of which are being applied in American bonds, while the remaining supports Chinese health and social security systems, Chinese banks solvability, internationalization of the Chinese economy, outward foreign direct investment (OFDI) and Chinese official foreign aid (ODA) to other developing countries. Although the Chinese OFDI fluxes are nowadays more oriented to mature economies, its bulk is mainly directed to partnerships with other developing countries like the African countries, and within those, the Chinese government identified one group strategically important to cooperate and invest, the Portuguese Speaking African Countries. These countries have high expectations on the Chinese investment and cooperation and our research questions are: (a) Should this investment be considered ODA or OFDI?; (b) How far can Chinese finance fluxes contribute to the development of these countries in terms of employment, exports, technology transfer?; (c) Is this investment seen as an opportunity or a threat by local people, is it fulfilling the created expectations or not? In this paper we concentrate our empirical research in Mozambiques case.